A hydrophilic interaction liquid chromatography–mass spectrometry (HILIC–MS) based metabolomics study on colour stability of ovine meat. (July 2016) - Subbaraj, Arvind K.; Kim, Yuan H. Brad; Fraser, Karl; Farouk, Mustafa M.
Abstract: Meat colour is one of the cues available to the consumer to gauge overall meat quality and wholesomeness. Colour stability of meat is determined by several factors both inherent to the animal and post-slaughter conditions, including ageing, storage/packaging and display times. A hydrophilic interaction liquid chromatography–mass spectrometry (HILIC–MS) based metabolomics study was undertaken to identify and compare polar metabolites between ovine meat samples that were exposed to different durations of ageing, storage conditions, and display times. Primary metabolites comprising amino acids, sugars, nucleotides, nucleosides, organic acids and their breakdown products were mainly identified as discriminating factors. For the first time, boron complexes of sugar and malic acid were also tentatively identified. As expected, most compounds identified were related to myoglobin chemistry, and compounds with antioxidant properties were found in higher levels in colour stable samples. Supplementary studies identifying semi-polar, non-polar and volatile compounds will provide a holistic understanding of the chemical basis of colour stability in ovine meat.